(3GdCfhGQ GdZQhjI aj TQM GddeYI GdOeTbjIs - (3eMeO LhGO Hf eMeO Jbj edG cJGHs ((3Ydj Hf eMeO GdebUhOjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3hHYO agPG ChGf GdTQhY aj eYGedGJ gPG GdcJGH GdeQShe HefjI GdCdHGH(B...s
(3BNQgG (B:s
(3hcaGjI GdTc GdehLH ddQLhY Edi Mce GdCUd hdh aj edGMXI EWdGbGJ GdfUhU hGdaJGhi, hGdMeO ddg(B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc(B: (3Ydj MajO GdgGOj cGTa GdZWGA, (B1371(3g`s
Keywords: (3abg GdePGgH GdCNQis